SOCIO-ECONOMIC WELLBEING THROUGH MICROCREDIT: AN IMPACT ANALYSIS OF SELECTED BENEFICIARIES FROM NATIONAL RURAL SUPPORT PROGRAMME - iram, afshan; Bibi Asab; Neelam Kubra; Muhammad Jamil (Journal of Peace, Development and Communication, 2023)
The main cause of Poverty, deprivation, and low standard of living in developing world are lack of capital and resources. Microcredit has been viewed as a powerful tool to combat poverty and help the destitute to reduce vulnerabilities, improve livelihood and nurture social and economic wellbeing. The existing study focused on the impact of national rural support programme on the socio-economic wellbeing of people in district Sargodha. The questionnaire was used to collect data form the microcredit beneficiaries. The sample size of 252 borrowers were selected through stratified random sampling and systematic random sampling technique. Descriptive analysis as well as parametric techniques were employed. It is found that national rural support program has significantly improved the indicators of economic wellbeing i.e., income, consumption, accumulation of assets and saving and statistically significant improvement in the value of social wellbeing i.e., improvement in children education, access to better health facilities, and improvement in the household general facilities.